Multifocal Tuberculosis with Prolonged Paradoxical Reaction: Assessment of the New Dengue Classification - Ebrahim K. Al-Ebrahim; Tariq A. Madani (Journal of King Abdulaziz University: Medical Sciences, 2019)
This is a case report describing successful treatment of a challenging case of an 18-year old previously healthy high school male student with multifocal tuberculosis involving the spleen and mediastinal and abdominal lymph nodes confirmed by histopathology of splenectomy tissue. The patient initially responded well to antituberculosis therapy with complete resolution of fever and improvement in his general health and weight. However, two months after initiation of anti-tuberculosis therapy, the patient developed paradoxical reaction manifest as recurrence of fever that persisted for five months and was associated with enlargement of lymph nodes. The fever failed to abate with continuation of the same antituberculosis therapy. Despite reassurance that the fever was due to a prolonged paradoxical reaction, a decision was made by the family to seek advice in another hospital where lymphoma was excluded again by histopathological examination of an excisional lymph node biopsy that revealed caseating granulomatous lymphadenitis and negative tuberculosis stain, culture, and polymerase chain reaction. The patient was continued on anti-tuberculosis therapy and treated with corticosteroids that resulted in complete resolution of fever and subsequent full recovery from his tuberculosis.